The spirit photographer : a novel - Varese, Jon Michael (New York : Overlook Duckworth, 2018)
While grifting mourners with photos that supposedly depict the spirits of their dead loved ones, an 1870 conman is shocked when he captures a real ghost that he recognizes as a woman he once knew, the daughter of an escaped slave.
Keywords: Spirit photography -- Fiction; Spiritualism -- Fiction; Boston (Mass.) -- History -- 19th century -- Fiction; Boston (Mass.) -- History -- 19th century -- Fiction; Historical fiction; Historical fiction